Բիքրոմատի թունազրկումը հողային միկրոօրգանիզմներով - Ե. Գ. Բաղդասարյան; Շ. Վ. Շալունց (ՀՀ ԳԱԱ հրատ.)
Հացահատիկային բույսերի (ցորեն, գարի) արմատային համակարգերից` ռիզոսֆերայից անջատված են միկրոօրգանիզմներ, որոնք ունեն Cr6+-ը մինչև Cr3+ վերականգնելու ֆերմենտային համակարգեր: Cr6+-ը մինչև Cr3+ վերականգնող ռեդուկտազն օժտված է բարձր ակտիվությամբ: Из корневой системы (ризосферы) зерновых культур (пщеницы, ячменя) выделены микроорганизмы, которые имеют ферментную систему, восстанавливающую Cr6+ до Cr3+, лишенного мутагенных и канцерогенных свойств. Объектом исследования служили аэробные грамотрицательные бактерии Pseudomonas aeruginosa. Выделенная из Pseudomonas aeruginosa редуктаза, восстанавливающая Cr6+ до Cr3+, обладает высокой активностью. The microorganisms have been separated that have fermentation systems of restoring Cr6+ up to Cr3+ from grain plants (wheat, barley) root systems. Cr3+ does not have toxic, mutagenic or cancerogenic properties. The aerobic gram-negative bacteria Pseudomonas ambigua have served as an object of the study. The results of the data indicate that the reductase restoring Cr6+ up to Cr3+ has a high of activity.
Keywords: Biology; Microbiology